(untitled) (Research, Society and Development, 2021)
This scientific work aimed to show the challenges that can be faced by the military police throughout their career and the importance of this professional who was transferred to the paid reserve or was retired for having acquired pathology due to the legal fulfillment of his duties in the Police Military of the State of Tocantins (PMTO) in defense of the society of Tocantins. In the end, it was proposed the elaboration of a draft State Law Project in order to recognize and institute the Military Police Veteran’s Day. The present proposal, when put into practice, will provide more recognition, prestige, appreciation and approximation of the military police officer with fellow members of the Institution who are in active service. Thus, if this proposal is instituted, it will be a way to annually honor the aforementioned professionals who, even at the risk of their own lives, dedicated themselves to the benefit of Tocantins society and left legacies for the Corporation’s history. In the work methodology, applied, descriptive, exploratory, bibliographical and documentary research was used, using the deductive method and carried out a qualitative approach. Therefore, the research concluded that the PMTO needs to prepare a draft State Law Project and manage with the Executive and Legislative Power of the State of Tocantins so that the Day of Military Police Veteran is instituted.